Does the EU Have a Future? - Sir William Nicoll (Romanian Journal of European Affairs, 2005)
While trying to give an answer to the question whether the European Union indeed has a future, the author analyzes the main stages of the integration process and examines past procedures and mechanisms in order to support his fundamental assumption that, because the EU is now so closely integrated, a “disunion” is unthinkable.